Ordinances of the city of Manchester. - Manchester (N.H.) (Manchester, N.H. Ruemely Press., 1847)
Vols. for 1909-24 include "A compilation of the public statutes relating to the government of cities and special acts relating to the city of Manchester."
Mode of access: Internet.
Keywords: Municipal charters -- New Hampshire -- Manchester; Ordinances, Municipal -- New Hampshire -- Manchester